Branje kot prostorska praksa - Vogrinčič Čepič, Ana (Ars et humanitas, 2019)
Despite the fact that the process of reading is always inscribed in time and place, studies of reading have traditionally focused on its mental dimension, i.e. on the interpretation of what has been read, and (with the exception of historical analysis and research on literacy) haven't dealt much with the direct physical reading environment. Based on individual in-depth interviews with readers about their reading habits, this article tries to pinpoint how the actual place of reading shapes the reading experience. It focuses on reading fiction for leisure and on reading at home, because this is what the participants themselves paid most attention to, but also deals with reading outdoors and in public, and touches upon the way the reading environment is changed by the process of digitisation. Throughout, the emphasis is on reading as an embodied and material practice. As it turns out, readers are not indifferent towards their immediate reading environments, and they usually consciously manage what and where will they read. It is very clear that they regard reading as a deeply sensorial experience. What importantly contributes to a better understanding of the topic are readers' memoires of their own readings, since they are often remembered together with vivid spatial detail. The conclusion reflects on prospects for future research on the environmental dimensions of reading, mainly with the use of personal memoirs.
Keywords: bralno doživetje; bralno okolje; intervjuji; sociologija branja; telesnost branja